The evolution of the mushy zone during the melting process of a binary nitrate salt. (October 2019) - Jiang, Dalang; Liao, Zhirong; Li, Pengda; Yu, Guoliang; Xu, Chao
Highlights: The melting process of a binary nitrate salt was experimentally investigated. The motion of the melting front and the mushy zone width were analyzed. Effect of heating temperature on the evolution of the mushy zone was studied. Two correlations were developed to predict the motion and width of the mushy zone. Abstract: In this study, an experimental setup was built to investigate the evolution of the mushy zone during the melting process of a binary nitrate salt (40% mol. LiNO3 -60% mol. KNO3 ). The thermophysical properties of the salt, including the solidus and liquidus temperatures and latent heat, were firstly determined. The melting process of the salt was then conducted in a thin container with one-sided heating. The temperature variations of the salt were measured and the change of the melting front were recorded by a digital camera for the melting processes under different heating temperatures. Based on the recorded transient locations, the moving rate of the melting front was calculated. The resulting moving rate, together with the measured temperatures, was further used to calculate the mushy zone width. Moreover, the effect of the heating temperature on the mushy zone was studied. The results show that the moving rate of the melting front decreases during the melting process while the mushy zone width increases. It is also found that the moving rate of the melting front increases while the mushy zone width decreases with the increasing heating temperature. Finally, both the dimensionless location of the melting front and the dimensionless mushy zone width during the melting process were developed as functions of Stefan and Fourier numbers.